2022
DOI: 10.3390/rs14205181
|View full text |Cite
|
Sign up to set email alerts
|

Flood Detection in Dual-Polarization SAR Images Based on Multi-Scale Deeplab Model

Abstract: The proliferation of massive polarimetric Synthetic Aperture Radar (SAR) data helps promote the development of SAR image interpretation. Due to the advantages of powerful feature extraction capability and strong adaptability for different tasks, deep learning has been adopted in the work of SAR image interpretation and has achieved good results. However, most deep learning methods only employ single-polarization SAR images and ignore the water features embedded in multi-polarization SAR images. To fully exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Earlier in this paper, we introduced the work of Nemni et al [4], Li et al [18], Zhao et al [30], Wu et al [46], Katiyar et al [47] and Kang et al [23] using CNN-based deep learning for the extraction of flood pixels from SAR images over different locations and environmental conditions. Comparing the results presented in these studies to our study, we found that our scores are either similar or superior to the scores presented.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier in this paper, we introduced the work of Nemni et al [4], Li et al [18], Zhao et al [30], Wu et al [46], Katiyar et al [47] and Kang et al [23] using CNN-based deep learning for the extraction of flood pixels from SAR images over different locations and environmental conditions. Comparing the results presented in these studies to our study, we found that our scores are either similar or superior to the scores presented.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kang et al [23] showed that the overall accuracy of FCN16 can reach 99%, which is comparable to our method. In another SAR-data-driven flood detection, Wu et al [46] achieved an average IoU score of 86.33% and PA score of 95.75%. Furthermore, the overall accuracy score in [46] appeared to be similar to that of Zhao et al [30], who achieved 95.95% for water and non-water classes, thus scoring about 3% lower than our best overall accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PSPNet network couples the semantic features of different areas via the pyramid pooling module and the pyramid scene parsing module, which elevates the segmentation precision of water body edges [5] . Deeplab series networks aggregate detailed information in the shallow layer and semantic information in the deep layer by using asymmetric structure [6] . SegFormer network realizes the semantic expression of higher-order water bodies by cutting off the positional encoding, utilizing MLP (Multilayer Perceptron) for feature extraction, and enlarging the receptive field [7] .…”
Section: Introductionmentioning
confidence: 99%